1992
DOI: 10.3354/meps088237
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation enzymes in Cyphoma gibbosum (Gastropoda: Ovulidae)- implications for detoxification of gorgonian allelochemicals

Abstract: The role of biotransformation enzymes in metabolism of lipophilic, dietary allelochemicals such as terpenoids and steroids has not been studied in marine organisms despite the significance of allelochemicals in the evolution of biotransformation enzymes and the importance of these enzymes in detoxification of anthropogenic xenobiotics. Here we report on cytochrome P450 and glutathione transferase (GST) from the digestive gland of Cyphoma gibbosum, a specialist predator that feeds on allelochemically rich gorgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 38 publications
2
38
3
Order By: Relevance
“…2 Recently, Thorton and Kerr 288 reported that high levels of predation by the mollusc Cyphoma gibbosum induced pseudopterosin C 81 production by Pseudopterogorgia elisabethae. While some experimental evidence suggests that C. gibbosum may use biotransformation enzymes to detoxify gorgonian metabolites, 262 this is the first instance where a specialist has been shown to induce the production of a gorgonian metabolite. Interestingly, induction did not occur after high levels of predation by the butterfly fish Chaetodon capistratus or artificial wounding of the sea fan.…”
mentioning
confidence: 91%
“…2 Recently, Thorton and Kerr 288 reported that high levels of predation by the mollusc Cyphoma gibbosum induced pseudopterosin C 81 production by Pseudopterogorgia elisabethae. While some experimental evidence suggests that C. gibbosum may use biotransformation enzymes to detoxify gorgonian metabolites, 262 this is the first instance where a specialist has been shown to induce the production of a gorgonian metabolite. Interestingly, induction did not occur after high levels of predation by the butterfly fish Chaetodon capistratus or artificial wounding of the sea fan.…”
mentioning
confidence: 91%
“…The high concentration of allelochemicals in gorgonian corals [27,[37][38][39][40], coupled with the findings that digestive glands of C. gibbosum contain high levels of GST activity [9], prompted an investigation to identify and biochemically characterize those GST enzymes possibly responsible for detoxifying gorgonian allelochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme activity was measured using CDNB as a substrate by the method of [32] optimized for C. gibbosum [9] …”
Section: Gst Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations